Growth and Morphological Traits for Two Lines of Native Japanese Chicken, Oh-Shamo - Oka , Takao (International Journal of Poultry Science, 2016)
Objective: This study investigated the morphological traits and growth patterns for two lines of Oh-Shamo. Methodology: A total of 31 offensive (OFF) line (17 males and 14 females) and 32 defensive (DEF) line (17 males and 15 females) were used. The body weight of each individual was recorded every week from hatching to 30 weeks old. In addition to measuring body weight, growth curves were estimated using the Gompertz function. Eight somatometrical measurements were recorded every 5 weeks. Results: It was shown that the estimated asymptotic body weight and somatometrical measurements in OFF line were larger than those in DEF one regardless of sex. It was found that significant increases of lengths in femur, tarsometatarsus and tibiotarsus in OFF males were longer than others (p<0.05) and the body weight and length/diameter of each body part in OFF groups was more than those in DEF ones and those in males were higher than in females (p<0.01). The lengths of tibiotarsus and tarsometatarsus were estimated as hypogrowth in the OFF male group, but as tachyauxesis in the DEF female group. Conclusion: These results suggest that there were significant differences between OFF and DEF in their somatotypes, especially in the tibiotarsus.